Local wisdom-based teaching material for enhancing primary students’ scientific literacy skill - Suryanti, Suryanti; Mariana, Neni; Yermiandhoko, Yoyok; Widodo, Wahono (Jurnal Prima Edukasia, 2020)
The study aims to develop local wisdom – based teaching materials to improve elementary school students’ scientific literacy skills, using a 4-D model: define, design, develop, and disseminate. The subjects of testing included 37 of fourth-grade students at SDN Gading 6 Surabaya. In addition, data were collected through validation sheets, tests of scientific literacy skills, and student questionnaires. The data analysis used descriptive statistics, N-gain, and different tests. The results showed that local wisdom – based teaching materials could be implemented as an alternative source of learning natural science in elementary schools, compliance with the criteria of a) valid in terms of fulfilling the 98% validity assessment score with very valid criteria b) practical reviewed from the 3.64 scores with very good criteria c) effective with a 0.5average N-gain, there are significant differences between the pretest and posttest scores,and 100% of positive responses.